2012
DOI: 10.3164/jcbn.11-103
|View full text |Cite
|
Sign up to set email alerts
|

Gingival vascular functions are altered in type 2 diabetes mellitus model and/or periodontitis model

Abstract: The association of vascular reactivity between diabetes and periodontal disease has not been clarified. Gingival blood flow was measured by laser Doppler flowmetry for 31 weeks in Wistar rats, Wistar rats orally challenged with Porphyromonas gingivalis (Wistar rats + Porphyromonas gingivalis), Goto-Kakizaki rats, and Goto-Kakizaki rats orally challenged with Porphyromonas gingivalis (Goto-Kakizaki rats + Porphyromonas gingivalis). Effects of alveolar bone resorption on periodontal tissue was enhanced in Wistar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 29 publications
2
47
1
1
Order By: Relevance
“…Whether the vasodilatory function of gingival microvessels can be used as a substitute measurement for the small vessel function in the same manner as in the skin model (17) needs further investigation, but our implemented heat provocation test could be a way to test this in human subjects. Our results are in concord with the findings of an animal experiment (53) where both the periodontal inflammation and diabetes per se influenced gingival vascular reactivity; therefore, we need to carefully distinguish between the effects of local inflammation and the systemic conditions.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Whether the vasodilatory function of gingival microvessels can be used as a substitute measurement for the small vessel function in the same manner as in the skin model (17) needs further investigation, but our implemented heat provocation test could be a way to test this in human subjects. Our results are in concord with the findings of an animal experiment (53) where both the periodontal inflammation and diabetes per se influenced gingival vascular reactivity; therefore, we need to carefully distinguish between the effects of local inflammation and the systemic conditions.…”
Section: Discussioncontrasting
confidence: 51%
“…neuropathy, nephropathy and retinopathy, were found to be associated with the presence of a more severe inflammatory pathology of periodontal tissues (49). A recent study (53) found decreased post-occlusive reactive hyperaemia in the gingiva of a diabetic rat compared to a healthy one and this response was further reduced by experimentally induced periodontitis. However, there is no direct evidence for the impairment of vascular reactivity in the human gingiva in periodontitis and/or DM.…”
mentioning
confidence: 99%
“…The pharmacokinetics of a nitroxyl compound (C-PROXYL) using in vivo L-band ESR was first reported by Berliner and Wan [45]. We also demonstrated that the decay rate constant of C-PROXYL was increased in association with oxidative stress by generating ROS [22], [23], [34]. Therefore, it was suggested that the treatment with acetic acid increased the generation of ROS in a local oral mucositis site.…”
Section: Discussionmentioning
confidence: 71%
“…Apart from being implicated in periodontitis [2-4], concepts of oxidative stress are being applied to explain the relationship between periodontitis and various systemic conditions such as metabolic syndrome [5], mitochondrial dysfunction [6], diabetes mellitus [7], and rheumatoid arthritis [8]. Interestingly, all of the associated systemic conditions have therapies focusing on the use of antioxidants to modulate or eliminate the disease [9,10].…”
Section: Introductionmentioning
confidence: 99%